A Combined Morphological and Molecular Evolutionary Analysis of Karst-Environment Adaptation for the Genus Urophysa (Ranunculaceae) - Xie, Deng-Feng; Cheng, Rui-Yu; Fu, Xiao; Zhang, Xiang-Yi; Price, Megan; Lan, Yan-Ling; Wang, Chang-Bao; He, Xing-Jin (Frontiers in Plant Science, 2021)
The karst environment is characterized by low soil water content, periodic water deficiency, and poor nutrient availability, which provides an ideal natural laboratory for studying the adaptive evolution of its inhabitants. However, how species adapt to such a special karst environment remains poorly understood. Here, transcriptome sequences of two Urophysa species (U. rockii and U. henryi), which are Chinese endemics with karst-specific distribution, and allied species in Semiaquilegia and Aquilegia (living in non-karst habitat) were collected. Single-copy genes (SCGs) were extracted to perform the phylogenetic analysis using concatenation and coalescent methods. Positively selected genes (PSGs) and clusters of paralogous genes (Mul_genes) were detected and subsequently used to conduct gene function annotation. We filtered 2,271 SCGs and the coalescent analysis revealed that 1,930 SCGs shared the same tree topology, which was consistent with the topology detected from the concatenated tree. Total of 335 PSGs and 243 Mul_genes were detected, and many were enriched in stress and stimulus resistance, transmembrane transport, cellular ion homeostasis, calcium ion transport, calcium signaling regulation, and water retention. Both molecular and morphological evidences indicated that Urophysa species evolved complex strategies for adapting to hostile karst environments. Our findings will contribute to a new understanding of genetic and phenotypic adaptive mechanisms of karst adaptation in plants.